2021
DOI: 10.3390/ijerph18126300
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibitory Control in Middle Childhood

Abstract: The main aim of this study was to investigate the development of selective inhibitory control in middle childhood, a critical period for the maturation of inhibition-related processes. To this end, 64 children aged 6–7 and 56 children aged 10–11 performed a stimulus-selective stop-signal task, which allowed us to estimate not only the efficiency of response inhibition (the stop-signal reaction time or SSRT), but also the strategy adopted by participants to achieve task demands. We found that the adoption of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 66 publications
(119 reference statements)
2
4
1
Order By: Relevance
“…Specifically, we found an increase in the use of the independent selective stopping strategy ( iDtS) and a decrease in the use of the global, non‐selective stopping strategy ( StD ) in preadolescents relative to younger children, with no differences between preadolescents and young adults. These findings suggest that preadolescence may be the endpoint of the maturation of processes needed to achieve task requirements underlying stopping selectively, in line with previous studies (Rincón‐Pérez et al., 2021).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Specifically, we found an increase in the use of the independent selective stopping strategy ( iDtS) and a decrease in the use of the global, non‐selective stopping strategy ( StD ) in preadolescents relative to younger children, with no differences between preadolescents and young adults. These findings suggest that preadolescence may be the endpoint of the maturation of processes needed to achieve task requirements underlying stopping selectively, in line with previous studies (Rincón‐Pérez et al., 2021).…”
Section: Discussionsupporting
confidence: 91%
“…(2021) found that for short SSDs, participants categorized as StD and dDtS showed failed stop RTs longer than go RTs (thus violating the independence assumption), but when SSDs were long both strategies showed failed stop RTs shorter than go RTs (the independence assumption was met). These results question prior procedures for categorizing subjects by individual differences in strategies (e.g., Bissett & Logan, 2014; Rincón‐Pérez et al., 2021; Sánchez‐Carmona et al., 2016; Sebastian et al., 2017), which assume that there are violations of independence at all SSDs in dDtS , and no violations of context independence in StD at any SSDs. In this light, differences in strategies might be an artefact of different individuals sampling different SSD distributions.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations